Реологічне моделювання розведених суспензій деяких патогенів у градієнтних течіях - Таран, Є.Ю.; Грязнова, В.О. (Видавничий дім "Академперіодика" НАН України, 2008)
The structure-phenomenological theory of a stressed state in aqueous dilute suspensions of rod-like pathogenic microorganisms is presented. The obtained rheological equation is used to study the rheological behaviour of a dilute suspension of viruses in a simple shear flow. As a result, it is demonstrated that such a suspension behaves itself as an elastoviscous liquid medium manifesting both the pseudoplastic dependence of the effective viscosity of the suspension on the shear rate and the Weissenberg effect.